Long Noncoding RNA–Messenger RNA (lncRNA–mRNA) Network in Resistance to Gummy Stem Blight (Stagonosporopsis cucurbitacearum) of Melon Plant Introduction (PI) 420145 - Rui Zhang; Jing Chen; Yongbing Zhang; Xiumei Lu; Chunyan Cheng; Ji Li; Qunfeng Lou; Yuhui Wang; Chuntao Qian (Horticulturae)
Gummy stem blight (GSB), caused by Stagonosporopsis cucurbitacearum (Didymella bryoniae), poses a growing threat to greenhouse melon production. Despite this, the defense mechanism of melon against S. cucurbitacearum remains poorly understood. In this study, by employing electron microscopy and transcriptome sequencing, we investigated the cellular ultrastructure differences and gene expression dynamics of two melon accessions, PI 420145 (resistant to GSB) and ‘Baipicui’ (susceptible), pre- and post- inoculation. Our results revealed that PI 420145 exhibits a thicker waxy layer on the leaf surface and limited conidial germination without obvious signs of cell damage compared to ‘Baipicui’. The transcriptomic analysis identified a total of 23,078 differentially expressed genes (DEGs) and 974 differentially expressed long noncoding RNAs (DELs). Specifically, phenylpropanoid biosynthesis, cyanoamino acid metabolism, and MAPK signaling–plant and plant–pathogen interactions were enriched in PI 420145, while ‘Baipicui’ displayed enrichment in metabolism and autophagy. Additionally, through lncRNA–mRNA network construction, we identified a total of 38 lncRNA–mRNA targeted regulatory relationships in the four most significant KEGG pathways for disease resistance.